The Effect off Listening Skill on the Speech Skill of Students in the Seventh Grade at Madrasah Tsanawiyah Mandailing Natal - Basri, Hasan; Yunaldi, Yunaldi (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2024)
The results of teaching listening and speech skills among students in the seventh semester of the Islamic Madarasah Tsanawiyah Mandailing Natal The existence of significant gaps in value. Pupils who reach the minimum completion criteria are minimal. Where there are students who have full listening and speech skill, and there are students who have full listening skill but speech skill is incomplete, and there are students who have incomplete listening skill but complete speech skill, and there are students who have incomplete listening and speech skill. This research is quantitative research using functional correlation design. The research community is all the seventh-grade students of the Islamic aesthetic middle school Mandailing Natal and sampling using Cluster Sampling. Analysis of results using the t-test. After completing the distributed data, it is natural and homogeneous. The results of this study can conclude that the average scores of the pupils increased from the pre-test (58.9) and the post-test (69.6) from the results of the hypothesis test analysis, obtaining t-hitung 9.109 and 1.699 t-tabel with a sig 2-tailed value obtained is <0.001 at a 95% confidence level or 5% error rate. The t-hitung is greater than the tabel (9.109 < 1.699). Based on these results, it can be concluded that the hypothesis is accepted, in the sense that there is a significant effect between the listening skill and the speech skill of the students in the seventh grade of the Islamic aesthetic middle school Ayk Naga Rasua Tabnoli Central.